Practice-Based Digital Marketing and Coding Training to Strengthen Students’ Entrepreneurial Competencies at Bina Satria School - Linda Wahyuni; Rika Rosnelly; Soeheri Soeheri; Chairul Rizal; Hardianto Hardianto; Andika Wiratama; Afandi Maulana (Ali Institute of Research and Publication, 2026)
This community service program implemented practice-based digital marketing and coding training to strengthen students’ digital entrepreneurship competencies at Bina Satria School. The program integrated experiential learning and project-based learning through website development using HTML, PHP, and MySQL, product catalog management, and digital promotion activities. Thirty students participated in six groups. Data were collected through observation, interviews, documentation, identical pre-test and post-test questionnaires, and project assessment. The 12-item questionnaire was reviewed by three experts. Internal consistency testing yielded Cronbach’s α = 0.683 and standardized Cronbach’s α = 0.715. Before the training, 83.3% of participants reported no or limited understanding; after the training, 73.3% reported understanding or high understanding. All six groups completed functional website projects with scores ranging from 88 to 91. The findings indicate an aggregate shift toward higher understanding and support the practical feasibility of integrating coding and digital marketing in contextual entrepreneurship training. Because the evaluation used categorical descriptive data without a comparison group or paired inferential analysis, the findings do not establish the program’s causal effectiveness.